Adverse Drug Reactions and Safety Profile of Common Over-The-Counter Drugs: A Review - Pranjali U. Mane; Sucheta S. Pawar; Maithili. S. Jadhav; Sayali C. Potdar; Shivani Lavate; Priyanka Sonwalkar; Bhagyashree Deshmane (Asian Journal of Pharmaceutical Research and Development, 2026)
Over-the-counter (OTC) medicines like paracetamol, omeprazole, cetirizine, and cyclopam are commonly used by people to treat everyday problems such as fever, pain, allergies, and acidity. These drugs are easily available and generally safe when taken correctly, but they can still cause unwanted side effects, especially when used for a long time or without proper guidance. As self-medication is becoming more common, people may not always be aware of these risks. Therefore, it is important to use OTC medicines carefully, follow recommended doses, and be aware of possible adverse drug reactions to ensure safe and effective treatment.